TMIC-31. ADI-PEG20 RESTORES IMMUNITY IN THE TUMOR MICROENVIRONMENT AND ERADICATES GBM TUMORS IN MICE WHEN COMBINED WITH RADIATION. (14th November 2022) - Symington, Jake; Perryman, Richard; Morse, Sophie; O'Neill, Kevin; Want, Elizabeth; Syed, Nelofer
Abstract: Glioblastoma (GBM) is a primary brain tumour with poor prognosis and limited treatment options. We previously demonstrated that arginine deprivation by ADI-PEG20 is effective in GBM tumors which are auxotrophic for arginine. We also reported that ADI-PEG20 has efficacy in arginine non-auxotrophic GBM when combined with radiation in the presence of an immune competent environment. Here, we present detailed mechanistic insight into our latter findings using multiplex Imaging Mass Cytometry (Fluidigm) and Spatial Transcriptomics (10x Genomics) of tumor samples treated with ADI-PEG20. ADI-PEG20 enhanced the expression on MHC class II on infiltrating CD11c+ dendritic cells and these cells colocalised specifically with CD4+ T cells. We also observed changes in the expression of PD-1/PD-L1 with ADI-PEG20 and this was further enhanced when ADI-PEG20 was combined with radiation. Moreover, combination therapy increased the expression of chemokines involved in immune cell recruitment and activation. Our findings demonstrate that arginine deprivation restores immune function in the tumor microenvironment of arginine non-auxotrophic GBM tumors and suggests that combinations with immunotherapies will further enhance efficacy for GBM tumors.